State Surveillance, Political Policing and Counter-Terrorism in Britain : 1880-1914. - Solomon, Vlad (Boydell & Brewer, Incorporated, 2021)
The formation of state surveillance and the emergence of institutionalized political policing in late Victorian and Edwardian Britain.
Description based upon print version of record.
Keywords: Intelligence service -- Great Britain -- History -- 19th century.; Intelligence service -- Great Britain -- History -- 20th century.; Terrorism -- Great Britain -- Prevention -- History -- 19th century.; Terrorism -- Great Britain -- Prevention -- History -- 20th century.; Terrorisme -- Grande-Bretagne -- Prévention -- Histoire -- 19e siècle.; Terrorisme -- Grande-Bretagne -- Prévention -- Histoire -- 20e siècle.; Intelligence service; Terrorism -- Prevention; Great Britain; 1800-1999; Electronic books.; History